Analisis Penggunaan Media Pembelajaran Digital pada Mata Pelajaran Matematika di SDN 82 Kota Bengkulu - Depi Helena; Niken Aprilia Azari; Wiwinda Wiwinda; Randi Randi; Fahrozi Ahmad (YASIN, 2026)
The limited use of digital instructional media in mathematics learning in elementary schools, particularly at SDN 82 Bengkulu City, indicates the need for learning strategies that are more concrete, interactive, and aligned with the characteristics of abstract mathematical content. This study aims to analyze the use of digital instructional media in mathematics subjects and to identify the obstacles faced in its implementation in Grade III of SDN 82 Bengkulu City. This study used a qualitative approach with a case study design. The research informants consisted of the principal, the Grade III mathematics teacher, and 29 Grade III students. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that digital instructional media, such as instructional videos, PowerPoint, and interactive images, had begun to be used in mathematics learning, but their implementation was not yet optimal and had not been carried out consistently. The use of these media helped students understand abstract material more concretely and increased their learning enthusiasm. The obstacles identified included limited facilities and infrastructure, uneven levels of teachers’ digital literacy skills, diverse student readiness, and internet network disruptions. The conclusion of this study emphasizes that digital instructional media play an important role in improving students’ understanding of mathematical concepts, but their implementation still requires optimization. The implications of this study indicate the need to improve technological facilities, strengthen teachers’ digital literacy competence, and develop more effective and sustainable digital-based learning strategies in elementary schools.